Morphological and Fractal Properties of Brain Tumors - Sánchez, Jacksson; Martín-Landrove, Miguel (Frontiers in Physiology, 2022)
Tumor growth is a complex process characterized by uncontrolled cell proliferation and invasion of neighboring tissues. The understanding of these phenomena is of vital importance to establish the appropriate diagnosis and therapeutic strategies and starts with the evaluation of their complex morphology with suitable descriptors. In the present work, scaling analysis is used for the extraction of parameters that characterize the tumor interface dynamics in brain tumors, such as fractal dimension and local roughness exponent. Results indicate in a definitive way that gliomas strictly behave as it is proposed by the Family-Vicsek ansatz, which corresponds to a proliferative-invasive growth model, while for benign tumors a proliferative growth model is more suitable. Other morphological and dynamical descriptors are used as a complementary view, such as morphological regularity, one-dimensional fluctuations represented as ordered series and bi-dimensional fluctuations of the tumor interface. These fluctuations were analyzed by Detrended Fluctuation Analysis to determine generalized Hurst exponents and fractal dimensions. In particular, complex visibility networks can be associated to the one-dimensional ordered series and support scaling analysis results providing a complementary description of tumor growth dynamics.